On the Van der Waals model on granular matters with truncated M-fractional derivative - Li, Wuzhuang; Rezazadeh, Hadi; Sabi'u, Jamilu; Akinyemi, Lanre; İnç, Mustafa (Springer, 2024)
In this work, exact solutions of the Van der Waals model (vdWm) are investigated with a new algebraic analytical method. The closed-form analysis of the vdW equation arising in the context of the fluidized granular matter is implemented under the effect of time-fractional M-derivative. The vdWm is a challenging problem in the modelling of molecules and materials. Noncovalent Van der Waals or dispersion forces are frequent and have an impact on the structure, dynamics, stability, and function of molecules and materials in biology, chemistry, materials science and physics. The auxiliary equation which is known as a direct analytical method is constructed for the nonlinear fractional equation. The process includes a transformation based on Weierstrass and Jacobi elliptic functions. Wave solutions of the model are analytically verified for the various cases. Then, graphical patterns are presented to show the physical explanation of the model interactions. The achieved solutions will be of high significance in the interaction of quantum-mechanical fluctuations, granular matter and other areas of vdWm applications.
Keywords: The auxiliary equation method; Van der Waals model; Traveling wave simulation; Solitary wave solution; Truncated M-derivative